The Dynamic and Reciprocal Relationship Between Problematic Internet Use and Loneliness: A Longitudinal Study - Marttila, Eetu; Koivula, Aki; Savolainen, Iina; Sirola, Anu; Oksanen, Atte (Informa UK Limited, 2026)
Problematic internet use (PIU) and loneliness are consistently linked, but whether one drives the other over time is unclear. Using six-wave panel data from 753 Finnish adults recruited through an online panel (4,518 observations), we examined how PIU and loneliness relate to each other within individuals. We used dynamic panel models that account for stable between-person differences and examine within-person changes, testing both contemporaneous (within-wave) and lagged (across-wave) associations over 6- and 12-month intervals. Results revealed strong reciprocal contemporaneous effects: when individuals experienced elevated PIU, they also reported greater loneliness, and vice versa. However, we found no evidence of lagged effects at either 6- or 12-month intervals. This suggests the relationship between PIU and loneliness unfolds within rather than across the specific measurement periods examined, though the contemporaneous effects may reflect unmeasured shorter-term dynamic processes occurring between waves.